Blended Learning Multimedia Development to Support English Training at Bina Nusantara University - Melania Wiannastiti (Bina Nusantara University, 2013)
In 2011, Bina Nusantara University put developing its people as the first priority, including developing English language proficiency. This development programs had been carried out since then. Some types of English trainings were given for the lecturers and staffs for some certain of times. Since the time provided for the trainings was limited, it was needed to support their language development by providing an autonomous learning through a website multimedia. This article aims to first describe the steps and result of the multimedia and second to find out whether the designed multimedia was useful for learners to develop their English. The multimedia focused on learning tenses which were needed in their field of work. The process was started by designing the objectives and the level of the target learners’ English proficiency. The process was continued by designing pre-test, the material, and the post test of each tense. To find out whether the designed multimedia was useful to develop the learners English the multimedia on simple present tense was tested to random respondents. By the end of applying this multimedia, a questionnaire was given to the respondents. The result was then analyzed qualitatively. The result shows that the multimedia on simple present tense is easy to follow and useful to develop their knowledge and skills in English.